Students' Experience of Online Learning during the COVID-19 Pandemic - Simamora, Roy Martin; Ramsul Nababan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The challenges faced by students in Indonesia during the COVID-19 pandemic when participating in online learning are essential things to consider. This research aims to reveal the limitations and obstacles they face in accessing and taking advantage of online education. Focusing on students' online learning experiences, this study seeks to identify barriers and offer recommendations for improvement. This research uses surveys at two different campus locations in Indonesia. The survey used an online questionnaire designed and reviewed by two researchers. This research focused on students aged 17 years and over. Initial data analysis includes the characterization of respondents based on age, gender, university, and significant using tables and graphs. Next, the researchers conducted descriptive analysis, calculated basic statistics, and categorized questions related to online learning. This research also examines the impact of campus location and its significant on student experiences. This study found that online learning did not meet expectations because technical and financial barriers prevented many students from accessing the Internet. These findings underscore the importance of providing affordable and easily accessible internet access and adequate devices for all students. The results of this research can guide education stakeholders in forming policies that enable students to engage in online learning effectively, especially during lockdowns and times of uncertainty caused by the pandemic.